Psychological experiences of placement in correctional facilities within the Western Cape Province of South Africa : an exploratory study of incarcerated youth - Slabber, Hester Jacoba (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.